Die trying a Jack Reacher novel - Child, Lee.; McClain, Johnathan, 1970- (New York : Penguin Audio, 2012)
Ex-military policeman Jack Reacher finds himself in the wrong place at the right time, as he finds himself kidnapped off of a Chicago street, along with an attractive woman who he was simply trying to help. As he and the woman are taken across the country, Reacher finds out that not only does the woman work for the FBI-- she's the Joint Chief of Staff chair's daughter. Lucky for them both, though, Reacher still has his military skill set and the drive to foil their captors.
Unabridged.
Read by Johnathan McClain.
Compact discs.
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Abduction -- Fiction; Audiobooks; Montana -- Fiction; Chicago (Ill.) -- Fiction; Political thrillers; Crime thrillers